Homeschooling: Indonesia New Trend of Islamic Education in the Global Era - Suyatno Suyatno; Ichsan Wibowo Saputro (Intelektual Pustaka Media Utama, 2017)
Nowadays, concept of school is not only in the formal school concept but also non-formal and informal school. Schooling at home (homeschooling) occur in Indonesia marks a new trend of education which is quite interesting to observe. Moreover, some homeschooling that occurred in recent years has identified itself as homeschooling that applied Islamic education concept. Moreover, the interesting side of this homeschooling is that it’s initiated by the former College Muslim Activists. The movement of College Muslim Activist is interesting to note further because of its role in the Islamization of the educational institutions in Indonesia. This article describes one educational model established by former College Muslim Activist, Homeschooling Group Khairu Ummah Bantul. The results showed that the establishment of Homeschooling Group Khairu Ummah Bantul motivated by four reasons, there are: (1) moral and religious reasons, (2) family unity reasons, (3) academic reasons, and (4) socialization reasons.